2005
DOI: 10.1590/s0034-89102005000400020
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade da atenção ao parto em maternidades do Rio de Janeiro

Abstract: Resumo ObjetivoAvaliar a qualidade da atenção durante o processo de trabalho de parto de acordo com normas da Organização Mundial de Saúde. Métodos Trata-se de estudo do tipo caso-controle, realizado em duas maternidades: pública e conveniada com o Sistema Único de Saúde, no Município do Rio de Janeiro. A amostra foi composta por 461 mulheres na maternidade pública (230 partos vaginais e 231 cesáreas) e por 448 mulheres na maternidade conveniada (224 partos vaginais e 224 cesáreas). De outubro de 1998 a março … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0
26

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 9 publications
2
28
0
26
Order By: Relevance
“…20 Oxytocin, on its turn, is frequently used for inducing and conducting labor. 21 Probably due to the low frequency of patients using misoprostol included in this study, no association with episiotomy was found. In relation to oxytocin, the non-association with episiotomy may be related to its indiscriminate use, in an attempt to shorten the labor time, an observation already described in another study conducted in Brazil, which has encountered a high frequency of oxytocin use.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…20 Oxytocin, on its turn, is frequently used for inducing and conducting labor. 21 Probably due to the low frequency of patients using misoprostol included in this study, no association with episiotomy was found. In relation to oxytocin, the non-association with episiotomy may be related to its indiscriminate use, in an attempt to shorten the labor time, an observation already described in another study conducted in Brazil, which has encountered a high frequency of oxytocin use.…”
Section: Discussionmentioning
confidence: 70%
“…In relation to oxytocin, the non-association with episiotomy may be related to its indiscriminate use, in an attempt to shorten the labor time, an observation already described in another study conducted in Brazil, which has encountered a high frequency of oxytocin use. 21 During the construction of this research's causal model, the hypothesis that birth at night shift would be a risk factor for episiotomy was suggested. However, this hypothesis was not confirmed and no studies showing this association were found in literature.…”
Section: Discussionmentioning
confidence: 99%
“…In some maternity wards, women are still forced to be confined to bed during labor and delivery. 26 However, it is known that women should be encouraged to adopt the position they prefer and desire. Ambulation and upright positions reduce the duration of labor and reduce the need for analgesia.…”
mentioning
confidence: 99%
“…This period is illustrated by a growth of studies on health evaluation, 2,24,33,35,36,67,72,74,87 and bioethics and gender. 34 Further developments were seen in the field with studies linking subjects such as violence and pregnancy, 22 HIV/AIDS and sterilization, 10 AIDS death and maternal deaths, 15 sexuality and sterilization, 94 and paternity and childcare.…”
Section: What the Scientific Production Is Aboutmentioning
confidence: 99%